Spintronics : a primer - Ansermet, Jean-Philippe (Boca Raton : CRC press, 2025)
"In order to engage in spintronics research, it is necessary to have sound understanding of magnetism, transport theory, and spin relaxation mechanisms. This textbook provides an introduction to these topics, in addition to providing an accessible overview of magnetic resonance, including coherence phenomena that are relevant for qubits dynamics and magnetic resonance in ferromagnets and antiferromagnets. This book will be a valuable resource for graduate students studying spintronics and related fields such as magnetism and spin waves, in addition to students of chemistry studying from nuclear magnetic resonance and groups specialized in simulation of advanced materials"--
Includes Glossary ,references and index
Keywords: Spin Relaxation Mechanisms; Magnetic, anisotropies; Coherent spin dynamics